2019
DOI: 10.1101/674259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subtype-specific and co-occurring genetic alterations in B-cell non-Hodgkin lymphoma

Abstract: B-cell non-Hodgkin lymphoma (B-NHL) encompasses multiple clinically and phenotypically distinct subtypes of malignancy with unique molecular etiologies. Common subtypes of B-NHL such as diffuse large B-cell lymphoma (DLBCL) have been comprehensively interrogated at the genomic level, but other less common subtypes such as mantle cell lymphoma (MCL) remain sparsely characterized. Furthermore, multiple B-NHL subtypes have thus far not been comprehensively compared to identify conserved or subtype-specific patter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…We immunized Tbl1xr1 D370Y/WT (D370Y/WT) or Tbl1xr1 WT/WT (wild-type [WT]) mice with the T cell-dependent antigen sheep red blood cells (SRBC) and sacrificed them at the peak of the GC reaction. Unexpectedly, although B cell abundance remained unaltered in D370Y/WT mice (Figure 1C; Data S1D and S1E), these animals showed significant decrease in the absolute number (p value = 0.0008; Data S1E) and proportion (Arthur et al, 2018;Ma et al, 2019;Reddy et al, 2017) and FL (Krysiak et al, 2017;Ma et al, 2019;Ortega-Molina et al, 2015). TBL1XR1-SMRT interacting region (Zhang et al, 2002) and PPI mutated positions are indicated.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We immunized Tbl1xr1 D370Y/WT (D370Y/WT) or Tbl1xr1 WT/WT (wild-type [WT]) mice with the T cell-dependent antigen sheep red blood cells (SRBC) and sacrificed them at the peak of the GC reaction. Unexpectedly, although B cell abundance remained unaltered in D370Y/WT mice (Figure 1C; Data S1D and S1E), these animals showed significant decrease in the absolute number (p value = 0.0008; Data S1E) and proportion (Arthur et al, 2018;Ma et al, 2019;Reddy et al, 2017) and FL (Krysiak et al, 2017;Ma et al, 2019;Ortega-Molina et al, 2015). TBL1XR1-SMRT interacting region (Zhang et al, 2002) and PPI mutated positions are indicated.…”
Section: Resultsmentioning
confidence: 92%
“…Information on TBL1XR1 mutation status in human lymphoma specimens was retrieved from publicly available datasets. DLBCL cases (Arthur et al, 2018;Ma et al, 2019;Reddy et al, 2017;Schmitz et al, 2018); FL cases: (Krysiak et al, 2017;Ma et al, 2019;Ortega-Molina et al, 2015). Clinic-pathological characteristics of these cases are detailed in the original publications.…”
Section: Human Subjectsmentioning
confidence: 99%
“…However, mutations within the HECT domain were found only in MCL tumors ( Figure 1A). 3 Patients with UBR5 mutations had between 4 and 12 additional mutations, but did not significantly cooccur with other mutations ( Figure 1B). 3 These findings suggest that HECT domain mutations of UBR5 are a disease-specific genetic feature of MCL.…”
Section: Ubr5 Mutations Are Specific To MCLmentioning
confidence: 96%
“…Recently, monoallelic mutations in the ubiquitin protein ligase E3 component n-recognin 5 (UBR5) were found in ;18% of patients with MCL. 3,4 Approximately 60% of mutations identified in UBR5 were frame shift mutations within its HECT domain, which can accept and transfer ubiquitin molecules to the substrate, leading to a premature stop codon before the cysteine residue associated with ubiquitin transfer.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have revealed additional transcription factors, corepressor/coactivator complex components, histone-modifying enzymes, chromatinremodeling complex components, and chromatin structural components that are targeted by genetic alterations in B-cell lymphoma. These alterations differ in frequency between histologies 1 and/or within transcriptionally or genetically defined subtypes, 2,3 function by perturbing epigenetic and transcriptional programs that control cellular pathways and cell fate decisions that are important for the tumor's cell of origin (reviewed elsewhere [4][5][6], and are potentially targetable by an increasing number of epigenetic-modifying agents. 7 Therefore, understanding the epigenetic basis for lymphoma is an important challenge due to the high potential for clinical translation that could improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%